Safety, Adequacy, and Accuracy of Transvaginal Ultrasound-Guided Tru-Cut Biopsy of Gynaecologic Tumours: A Retrospective Single-Centre Study - Munachiso Iheme Ndukwe; Dominik Karasek; Denisa Pohanková; Ivan Praznovec; Petra Bretova; Martin Stepan; Dominik Habes; Jan Laco; Akaninyene Eseme Ubom; Milan Vosmik; Igor Sirak (Diagnostics)
Objective: To evaluate the safety, adequacy, and accuracy of tru-cut biopsy of gynaecologic tumours in a population of Czech women. Methods: A four-year retrospective study of ultrasound-guided tru-cut biopsy of gynaecologic tumours was conducted in the Department of Obstetrics and Gynaecology, Charles University, Hradec Kralove, Czech Republic. Results: One hundred and four women with gynaecologic tumours underwent transvaginal tru-cut biopsy within the study period. The most common indication for tru-cut biopsy in more than one-half of the women was a suspicion of malignancy/inability to exclude malignancy (59, 56.7%). Most of the tumours were malignant on histopathological examination (71, 68.3%), with advanced ovarian cancer being the most common type of malignancy (43/71, 60.6%). The overall adequacy and accuracy rates of tru-cut biopsy were 93.3% and 93.3%, respectively. Most of the inadequate samples were obtained from overweight and obese women (5/7, 71.4%), with only one biopsy sample taken in the majority of the inadequate biopsies (5/7, 71.4%). Accuracy was higher for malignant than benign tumours (97.7% vs. 82.4%). For malignant tumours, accuracy was highest for advanced ovarian cancers (33/40, 82.5%). Only one case was complicated by bleeding, giving an overall complication rate of 1%. The complicated biopsy was taken by a gynae-oncology trainee. Conclusions: Tru-cut biopsy is a cost-effective and safe preoperative diagnostic modality for patients with gynaecologic tumours, offering high adequacy and accuracy. It is particularly useful in patients with advanced ovarian cancer, most of whom present late with inoperable tumours that contraindicate primary surgery.